Occipital Emissary Foramina in South Indian Modern Human Skulls. (20th February 2013) - Singhal, Suruchi; Ravindranath, Roopa
Abstract : An occipital emissary foramen has been traditionally described as a foramen present in the squamous part of the occipital bone at the occipital protuberance transmitting a vein that connects the confluence of sinuses with the occipital vein. The present study was done on 221 South Indian adult modern human skulls of unknown sex in the Department of Anatomy, St John's Medical College, Bangalore, India. The foramen was observed in 21/221 (9.50%) skulls, 6/21 (28.57%) to the right of, 10/21 (47.61%) to the left of, and 2/21 (9.52%) on the External Occipital Crest. It was seen more often near the posterior margin of foramen magnum rather than at the External Occipital Protuberance as has been traditionally described. A new finding is that bilateral foramina were observed in 3 skulls (14.28%). The incidence was higher than seen in other Indian population. Since it is present near the foramen magnum in most cases, knowledge of the number and position of the foramen is important for suboccipital craniotomies. The extensive connections of the veins with cranial venous sinuses may lead to intracranial infections and vice versa.